Logan Pryce makes a mess - Gilmore, Grace (Gilmore, Grace. Tales from Maple Ridge., 2015)
"When his father is hired for a temporary job at the general store, farm boy Logan can't wait to lend a hand. But his eagerness may cause his dad to lose this job. Can Logan's mistake be fixed in time?"--